PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS KONTEKSTUAL DENGAN MENANAMKAN NILAI-NILAI KEISLAMAN PADA MATERI SISTEM REPRODUKSI UNTUK KELAS XI MAN 1 KERINCI - Devita Rosadi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Reproduction system items relate to everyday life and a lot of sentences of alqur'an which can be integrated study to can remain to relate values of islam. MAN 1 Kerinci seen that teaching materials used by teacher still have the character of teacher and public do not have teaching materials which relate values of islam. so that study reproduction system items which is tend to theoretical and seldom be developed by connecting items with problem of social exist in environment. Pursuant to the mentioned, so the research with aim to yield product in the form of LKPD base on Kontekstual by inculcating values of islam. Developed LKPD using model of EDDIE. Data collecting with validated by expert and practitioner, That it was tried out on a limited basis in class XI MIPA 1 and MIPA 2 MAN 1 Kerinci to know the pacticality and effectiveness. Based on the result of this research, it was known that the LKPD is in very valid level. The practicability test of the LKPD is in very practice. The effectiveness of the LKPD can be seen from the students activities and cognitive, evaluation were in very good criteria. The conclusion of this research is the LKPD contextual based inculcating value of islam of reproduction system was declared valid, practice, and effective.